Pemberdayaan Penerima Manfaat Program Keluarga Harapan (PKH) di Desa Lamglumpang dalam Produksi Sabun Antibakteri Berbahan Ampas Kopi dan Minyak Nilam - Fajar Fakri; Didi Nurhadi Illian; Cut Nella Asyifa; Mirdha Iryana; Muhammad Amin Nasution (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Coffee is one of Indonesia's leading commodities, making it the world's largest coffee producer. In Aceh, the culture of drinking coffee has become part of people's daily traditions, especially in Ulee Kareng Sub-district, which is known as one of the centers of coffee bean powder processing. Large amounts of coffee grounds are produced during the coffee processing process, but they are typically not utilized optimally and often end up as waste. We have the potential to process coffee grounds into value-added products like antibacterial soap. Furthermore, patchouli oil from patchouli plants growing in Aceh has strong antibacterial properties, making it an ideal ingredient for combining with coffee grounds in making antibacterial soap. This community service activity aims to empower the beneficiaries of the Family Welfare Program (PKH) in Lamglumpang Village by improving their skills in making antibacterial soap formulated from coffee grounds and patchouli oil. The training provided is in the form of making dish soap products, as well as understanding the economic potential of these ingredients. The activity stages include socialization, technical training, application of simple technology in production, as well as mentoring and evaluation of product results. Results showed high enthusiasm from participants, with active involvement in the training and a desire to continue soap production independently. We expect this program to create new economic opportunities, enhance the economic independence of the Lamglumpang Village community, and lessen their reliance on social assistance. This antibacterial soap innovation also supports waste reduction and sustainable utilization of local resources.